Analysis Debt Outside Country In Growth Economy Indonesia - S Safrizal; J Julianti (Apollo: Journal of Tourism and Business, 2023)
Objective drafting work scientific This is analyze review on influence foreign debt in economic development in Indonesian. Economic development can what is meant is the growth of activity in the economy that creates goods and services made in society increases so that the prosperity of citizens keep getting big. The procedure used is descriptive use approach qualitative, with a descriptive research design on the research model used. The results review displays if debt outside country share donations in economic development but would be better if government can heighten investment ability which are contained. Impact debt outside country on period short no influence in a manner significant to development economy in Indonesia. Management debt outside country it feels like can held best- good so that no burden country with collecting loan payments made, so this research reveals that foreign debt decisions need to be re-examined with various aspects of feasibility analysis of foreign debt actions